Philippine government : development, organization and functions - Zaide, Gregorio F. (Manila : The Modern Book Company, 1967)
This book is a survey of the government of the Republic of the Philippines, its origin and development, its organization, and its function.
Introduction -- Pre-Spanish government -- Philippine government during the Spanish period -- The First Philippine Republic -- American military government -- Development of Philippine autonomy -- The Philippine independence law -- The Constitution of the Philippines --The Commonwealth of the Philippines -- Philippine government during the Japanese occupation -- The Republic of the Philippines -- The Congress of the Philippines -- The Judiciary -- National administration -- Provincial government -- Municipal government -- Chartered cities -- Financing our republic -- Political parties in the Philippines -- Suffrage and elections -- Filipino citizenship -- Duties and rights of the people -- Foreign relations of our republic -- Our republic in world affairs
Includes index.
Keywords: PHILIPPINES -- POLITICS AND GOVERNMENT